Research and Modernization of Inspection and Monitoring Practices for Pipeline, Casing, and Tubing - Nnadikwe Johnson; Samuel Hanotu Kwelle (Jurnal Teknik Indonesia, 2025)
This research investigates the modernization of inspection and monitoring practices for pipeline, casing, and tubing. The study focuses on the development and implementation of advanced inspection techniques to detect defects and imperfections such as cracks, dents, and diameter reduction, which can have devastating consequences for human safety, the environment, and the soil. The research aims to establish a comprehensive framework for the modernization of inspection and monitoring practices, encompassing the latest technologies and data analytics to ensure the integrity and reliability of pipeline, casing, and tubing infrastructure. The outcome of this research will provide a benchmark for the minimum inspection requirements, setting a new standard for the industry to ensure safe and sustainable operations.